Crystal structure of 1,2-bis(2,2,3,3,5,5,5-heptamethyl-1,1,4,4- tetrakis(trimethylsilyl)pentasilan-1-yl)ditellane, C38H114Si18Te2 - Qi Fan; Xiao Xu-Qiong (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C38H114Si18Te2, triclinic, P1‾$\overline{1}$ (no. 2), a = 9.0857(18) Å, b = 9.7412(19) Å, c = 24.213(5) Å, α = 94.25(3)°, β = 95.26(3)°, γ = 117.58(3)°, V = 1874.9(6) Å3, Z = 1, Rgt(F) = 0.0425, wRref(F2) = 0.1580, T = 296(2) K.